25 jaar Rode Leeuwen : een kwarteeuw Vlaams socialisme in de hoofdstad - Bracquené, Wouter; Galle, Marc; Fayat, Hendrik; Peiren, Luc (Brussel: SP-Brusselse Hoofdstedelijk Gewest, 1993)
"Archief Vandenabeele Werner"